Snow Dog - Blackman, Malorie (London Corgi Pups, 2001)
"It's going to be woof-onderful!" There is nothing Nicky wants more in the world than a dog to play with. But Mum and Dad don't want one. Then Grandad has an idea - he and Nicky can MAKE a dog: a snow-dome dog. Even better, he has some special clay, found at the end of a rainbow, so that the dog will be extra -special. Maybe even magic... - Publishers description.
Include Illustrations
Keywords: Illustrated by Sami Sweeten